Anguillicola crassus Infection Significantly Affects the Silvering Related Modifications in Steady State mRNA Levels in Gas Gland Tissue of the European Eel - Pelster, Bernd; Schneebauer, Gabriel; Dirks, Ron P. (Frontiers in Physiology, 2016)
Using Illumina sequencing, transcriptional changes occurring during silvering in swimbladder tissue of the European eel have been analyzed by comparison of yellow eel and silver eel tissue samples. Functional annotation analysis based on GO terms revealed significant expression changes in a number of genes related to the extracellular matrix, important for the control of gas permeability of the swimbladder, and to ROS (reactive oxygen species) defense, important to cope with reactive oxygen species generated under hyperbaric oxygen partial pressures. Focusing on swimbladder tissue metabolism, levels of several mRNA species encoding glucose transport proteins were several-fold higher in silver eels, while enzymes of the glycolytic pathway were not affected. The significantly higher steady state level of a transcript encoding for membrane bound carbonic anhydrase, however, suggested that CO2 production in the pentose phosphate shunt and diffusion of CO2 was of particular importance in silver eel swimbladder. In addition, the mRNA level of a large number of genes related to immune response and to sexual maturation was significantly modified in the silver eel swimbladder. The modification of several processes related to protein metabolism and transport, cell cycle, and apoptosis suggested that these changes in swimbladder metabolism and permeability were achieved by increasing cell turn-over. The impact of an infection of the swimbladder with the nematode Anguillicola crassus has been assessed by comparing these expression changes with expression changes observed between uninfected yellow eel swimbladder tissue and infected silver eel swimbladder tissue. In contrast to uninfected silver eel swimbladder tissue, in infected tissue the mRNA level of several glycolytic enzymes was significantly elevated, and with respect to extracellular matrix, several mucin genes were many-fold higher in their mRNA level. Modification of many immune related genes and of the functional categories ‘response to DNA damage stimulus’ and ‘cellular response to stress’ illustrated the damaging effect of the nematode infection. This study has identified a range of cellular processes in the swimbladder of silver eels that appear to be altered by nematode infection. These altered cellular processes could contribute to detrimental changes in swimbladder function that, in turn, may lead to impairment in spawning migration.